Concurrent Expert Evidence, an Australian Forensic Pathology Experience. Issue 4 (December 2015) - Day, Christopher; Little, Dianne
Concurrent witness evidence or "hot tubbing" is a novel method of delivering expert witness evidence. It has been used primarily in civil litigation cases where evidence is tendered to the court by experts in a panel-style discussion. Experts from similar disciplines and often from competing interests are asked to give evidence together in an attempt to better understand the issues at hand and give clarity to areas of agreement and disagreement. In our experience, this method is of benefit, allowing key issues to be highlighted in a timely and efficient manner. Our experience of hot tubbing is relatively unique in the setting of forensic pathology and we present a case where evidence was given in this manner and briefly review its application.